PP-003 Endoscopic retrograde cholangiopancreatography in renal patients: a case control study of complication rates. (23rd September 2015) - Pattni, S; Dhar, A; Monahan, K J; Vlavianos, P; Westaby, D
Abstract : Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) remains a high-risk procedure with a significant incidence of procedure related complications. Endoscopy in patients with renal disease has additional associated morbidity. The aim of the study was to determine the incidence of procedure related complications following ERCP in a cohort of patients with end stage renal disease receiving dialysis (ESRD) and renal transplant recipients (RT). Methods: A retrospective analysis of patients under the care of the largest renal unit in Europe, who underwent ERCP during a 36-month period. A cohort of patients without renal disease, matched for age, sex, comorbidities, indication, procedural intervention and results were used for comparison. Results: 51 ERCPs were performed on ESRD and RT patients, and 100 case control matched ERCPs were randomly selected retrospectively over the study period. 35 ERCPs were performed on ESRD patients (median age 66.7, M/F ratio 1.9:1). Sphincterotomies were performed in 65.7% (23/35) of procedures. There was a significant increased risk of post-sphincterotomy bleeding in the ERSD group vs the control group (6/23 vs 2/56, p<0.01) and a significant increased risk of post ERCP pancreatitis (9/35 vs 9/100, p<0.05). 16 ERCPs were performed on RT patients (median age 64.5; M/F ratio 1.3:1). Sphincterotomies were performed in 50.0% (8/16) of procedures. There was a significant increase in the risk of post sphincterotomy bleeding in the RT group vs the control group (3/8 vs 2/56, p<0.05) and a significant increased risk of post ERCP pancreatitis (5/15 vs 9/100, p<0.05). No patient related factors were related to the incidence of post ERCP pancreatitis in ESRD nor RT patients, and the absence of a sphincterotomy was the only procedural related factor significantly related to the incidence of post ERCP pancreatitis in either group (OR 1.46, 95% CI 1.06 to 2.00). ERSD patients had a significant increase in 30-day procedural related morbidity vs control group (17/35 vs 17/100, p<0.001, OR 4.05, 95% CI 1.74 to 9.46). There was no significant increase in 30-day procedure related morbidity in RT patients vs the control group. No significant increase in 30-day mortality was demonstrated between the ESRD nor the RT group and the control group. Conclusion: ERCP in both ESRD and RT patients is a high-risk procedure with a significant added incidence of post ERCP pancreatitis and post sphincterotomy bleeding. These findings suggest that ERCP and sphincterotomy should be approached with caution in this select group of patients, and measures targeted to minimise the risk of these complications should be employed.